Paleoenvironment and shale gas potential of the Carboniferous Dawuba and the Cambrian Niutitang shales in the Upper Yangtze Platform, South China - Wang, Ting; Xu, Zhengjian; Yuan, Kun; Wang, Xunlian; Ge, Mingna (Frontiers in Earth Science, 2024)
Marine shale gas has emerged as a prominent unconventional petroleum resource in recent years, known for its abundant reserves and energy potential. Based on the database of geochemical, mineralogy and physical lab measurements, this study investigates the paleoenvironmental conditions and shale gas potential of the Carboniferous Dawuba and Cambrian Niutitang shales in the Upper Yangtze Platform, South China. Analysis of the paleoclimate and water conditions reveals that the Dawuba shale was deposited under a warm and arid climate with reducing conditions that favored organic matter (OM) preservation, transitioning towards marine conditions with increasing salinity. The Niutitang shale experienced a cooler, arid climate with prevalent saltwater and reducing conditions, also conducive to OM preservation. Both formations have reached the post-mature stage, displaying good to excellent source rock potential. The Dawuba shales are characterized by Type II2 kerogens, while the Niutitang shales predominantly contain Type I kerogens, indicating high gas generation potentials for both. The formations are composed of mixed and argillaceous shales, exhibiting ultra-low porosity and permeability but featuring development of dissolution pores, OM pores, and micro-fractures essential for gas storage. Comparative analysis shows the Dawuba shales have superior BET-specific surface areas, total pore volumes, and average pore diameters than the Niutitang shales. However, gas contents in both formations are relatively low, underscoring the necessity for further research on shale gas preservation conditions. The Qiannan Depression in Guizhou, particularly the Shangyuan and Zongdi areas of the Dawuba Formation, are identified as promising regions for shale gas exploration due to favorable geological characteristics. This study highlights the significant shale gas potential in the Upper Yangtze Platform and calls for focused research to optimize exploration and extraction efforts.